Upaya Markaz Inayah dalam Meningkatkan Kualitas Ibadah Umrah Warga Negara Indonesia melalui Program Madrasah Umrah - Muhamad Saddam Nurdin; Benjamin Franklyn (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This Community Service Program (PkM) aims to improve the quality of the Umrah pilgrimage for Indonesian citizens through the Umrah Madrasah program implemented by Markaz Inayah. Markaz Inayah initiated the Umrah Madrasah program which focuses on the spiritual and intellectual development of participants with learning methods or education in preparation for the Umrah pilgrimage. This program is carried out regularly, with a frequency of three times a year and a duration of one month. This program component consists of four elements, namely distribution of reading materials, study of religious knowledge, cult, and visits to historical locations in Mecca and Medina. This activity is carried out before the Umrah pilgrims leave for Mecca to carry out the Umrah pilgrimage. The result of this activity is that the congregation can carry out the Umrah pilgrimage in accordance with Islamic law. Although there are several obstacles faced in implementing this activity, these obstacles can be anticipated and overcome by developing solutions that are appropriate and adaptive to the prevailing field conditions.